Effects of feeding different levels of ocimum basilicum seeds on per-formance and immune traits of broiler - Mohammed, Zahid I.; Kadhim, Kadhim S.; Taher, Maisaa G. (Journal of Kerbala for Agricultural Sciences, 2017)
This study was conducted to evaluate the effect of Ocimum Basilicum seeds supplementation of a commercial broiler diet on the performance and immune response. Three dietary treatments(100 birds/treatment) with two replicates (50 birds/ replicate) one day old straight run Ross 308 . T1 (as control group) birds fed basal diet without any additives. While, T2 and T3 fed diet supplemented daily with 0.3 and 0.6% basil seeds respectively to the end of the experiment (42 days) to investigate the broiler performance and antibody titer against Newcastle disease virus (NDV) and infectious bronchitis (IB). Results showed that the two levels of Ocimum Basilicum seeds supplementation (0.3 and 0.6%) had a beneficial effect on the antibody titer against (NDV) and (IB) and the high level (0.6%) was more significant against (NDV) while the low level (0.3%) was more significant against (IB). The high levels of antibodies titers were considered as the indicative of antiviral activity of O. Basilicum seeds. in addition, The results revealed significant (p<0.05) improvement of feed conversion ratio and high liver weight and spleen index in treatment groups compared with control group. In conclusion, Ocimum Basilicum seeds supplementation in commercial broiler diets was beneficial to broiler performance and immune function.